The Use of Short Animation Film to Improve The Students’ Narrative Writing Ability of The Eight Grade Students of SMP Negeri 5 Pinrang - Hamji, Adi Aris (La Parole : Journal of Language Teaching and Pedagogy, 2018)
This research based on the students’ problem related to English teaching especially in students’ writing ability. It was caused by the teaching media of the teacher in classroom was not interesting for students. It was also caused by several factors such as the students still take a lot of time to write because they do not know what they will written on their paper. In addition, writing is difficult lesson because in writing, we not only share our ideas from our mind but also we have to choose and combine the vocabulary well to make a writing that is meaningful. And one of the writing texts that have to be learnt in SMP is narrative text. Therefore, the objective of the research was to find out whether there is an improvement students’ narrative writing ability after being taught through animation film. This research applied quasi-experimental design with two groups namely experimental and control class. The population of this research was the eighth grade students of SMP Negeri 5 Pinrang academic year 2017/2018. The sample of this research consisted of 28 students from two classes taken from the population of the eighth grade students of SMP Negeri 5 Pinrang by using purposive sampling technique. The result of the data analysis showed that the students’ narrative writing ability improved. It showed by mean score of pre-test was 41.00 and post-test was 72.21. it showed that the writing ability of the eighth grade student of SMP Negeri 5 Pinrang improved by using animation film. After analyzing the data by using SPSS version 20, the result of probability value in post-test was 0.00 and significance value was 0.05. It means that that the probability value (0.00) was lower than significance value (0.05). Those indicated that H 0 was rejected and H1 was accepted. It means that the eight grade students of SMP Negeri 5 Pinrang for experimental class was significantly different. In conclusion, teaching writing by using animation film was effective to improve the eighth grade students of SMP Negeri 5 Pinrang of academic year 2017/2018.